Penegakan Hukum Terhadap Tindakan Penolakan Pemakaman Jenazah Korban Covid-19 Dalam Perspektif Hukum Positif - Siti Nur Aini (Fakultas Hukum Universitas Wahid Hasyim, 2024)
Law enforcement regarding the act of refusing to bury the bodies of Covid-19 victims is a crucial issue in the context of the global pandemic. This rejection occurs due to public concerns about virus transmission, which is often triggered by a lack of correct understanding and information. From the perspective of Indonesian positive law, this act of refusing burial can be considered a violation of basic human rights, including the right to a decent burial. This article examines the relevant legal aspects, including applicable laws and regulations as well as the responsibilities of the government and society in ensuring these rights are fulfilled. With a normative juridical approach, this research highlights the importance of public education and strict law enforcement to prevent discrimination against Covid-19 victims. The results of the study show that even though there are clear regulations, implementation in the field still faces significant challenges, especially in terms of coordination between institutions and outreach to the community.